Probabilistic human health risk assessment of PM2.5 exposure in communities affected by local sources and gold mine tailings - Thabethe, Nomsa Duduzile Lina; Makonese, Tafadzwa; Masekameni, Daniel; Brouwer, Derk (Frontiers in Public Health, 2025)
Epidemiological studies have found that exposure to fine particulate matter (PM2.5) poses potential human health risks, including respiratory, cardiovascular and cerebrovascular diseases. This study aimed to assess the potential human health risks associated with exposure to PM2.5 in the eMbalenhle community which is near gold mine Tailings Storage Facilities (TSFs). Ambient PM2.5 concentrations were measured for 1 year (from February 2022 to February 2023) using the Clarity Node-S low-cost monitor (LCM). The United States Environmental Protection Agency (USEPA) equations were used to estimate the carcinogenic and non-carcinogenic health risks associated with exposure to PM2.5 in toddlers, children, adults and the older adult. Lastly, a probabilistic Human Health Risk Assessment (HHRA) model, which employs Monte Carlo simulations (MCS), was applied to assess the sensitivity and uncertainty risks. The annual PM2.5 Geometric Mean (GM) concentration were 17, with a Standard Deviation of (SD) of 10.4 and a Geometric Standard Deviation (GSD) of 1.69 μg/m3. This was below the South African annual National Ambient Air Quality Standards (NAAQS) of 20 μg/m3. However, this concentration exceeded the World Health Organization (WHO) guidelines and the USEPA annual limit values of 5 and 9 μg/m3, respectively. For the WHO guidelines, South African and USEPA NAAQS, the HQ was highest at the 95th percentile for all subgroups. For the South African NAAQS, the HQ was estimated to be 0.9 for all subgroups, indicating safe levels. When utilizing the USEPA NAAQS, a value of 2.5 was reported, while the WHO guidelines recorded the highest HQ of 3.5, indicating unsafe levels. This demonstrated that the SA NAAQS underestimated exposure to PM2.5 concentrations. Probabilistic HHRA assessed potential cancer risk (CR) due to continuous exposure to PM2.5 concentrations. For both male and female elders, the CR was approximately 1 in 10, meaning that about 100,000 out of 1,000,000 exposed elders were at an increased risk of developing cancer over their lifetime. The study recommends revising the current South African PM2.5 NAAQS to adopt more stringent measures and align them to international benchmarks to safeguard the public from adverse health effects due to PM2.5 exposure.